Community health workers' perspectives on integrating into school settings to support student health - Yao, Nicole; Kowalczyk, Monica; Gregory, LaToya; Cheatham, Jeannine; DeClemente, Tarrah; Fox, Kenneth; Ignoffo, Stacy; Volerman, Anna (Frontiers in Public Health, 2023)
While schools represent key venues for supporting health, they continue to experience gaps in health resources. The integration of community health workers (CHWs) into schools has the potential to supplement these resources but has been underexplored. This study is the first to examine perspectives of experienced CHWs about how CHWs can be applied in school settings to support student health. This qualitative study involved conducting semi-structured interviews focused on implementation of CHWs in schools with individuals who held positions aligned with the CHW scope of work. De-identified transcripts were analyzed, and codes were organized into domains and themes. Among 14 participants, seven domains emerged about the implementation of CHWs in schools: roles and responsibilities, collaborations, steps for integration, characteristics of successful CHWs, training, assessment, and potential challenges. Participants shared various potential responsibilities of school-based CHWs, including educating on health topics, addressing social determinants of health, and supporting chronic disease management. Participants emphasized the importance of CHWs building trusting relationships with the school community and identified internal and external collaborations integral to the success of CHWs. Specifically, participants indicated CHWs and schools should together determine CHWs’ responsibilities, familiarize CHWs with the school population, introduce CHWs to the school community, and establish support systems for CHWs. Participants identified key characteristics of school-based CHWs, including having familiarity with the broader community, relevant work experience, essential professional skills, and specific personal qualities. Participants highlighted trainings relevant to school-based CHWs, including CHW core skills and health topics. To assess CHWs’ impact, participants proposed utilizing evaluation tools, documenting interactions with students, and observing indicators of success within schools. Participants also identified challenges for school-based CHWs to overcome, including pushback from the school community and difficulties related to the scope of work. This study identified how CHWs can have a valuable role in supporting student health and the findings can help inform models to integrate CHWs to ensure healthy school environments.